2021
DOI: 10.1093/infdis/jiab003
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Respiratory Syncytial Virus Infection in Healthy Adults by a Single Immunization of Ad26.RSV.preF in a Human Challenge Study

Abstract: Background Respiratory syncytial virus (RSV) is a significant cause of severe lower respiratory tract disease in children and older adults, but has no approved vaccine. This study assessed the potential of Ad26.RSV.preF to protect against RSV infection and disease in an RSV human challenge model. Methods In this double-blind, placebo-controlled study, healthy adults aged 18–50 years were randomized 1:1 to receive 1x1011 vp Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 29 publications
(39 reference statements)
3
45
0
1
Order By: Relevance
“…The vaccine consists of two components: a replication-deficient adenovirus (Ad26) expressing the RSV prefusion F protein (preF) and soluble recombinant preF protein. Administered intramuscularly, the vaccine has previously been shown to induce robust humoral and cellular immunity ( Williams et al, 2020 ) and the Ad26.RSV.preF component alone shown to provide protection in a controlled human challenge model ( Sadoff et al, 2021 ).…”
Section: Short Presentations: Preventionmentioning
confidence: 99%
“…The vaccine consists of two components: a replication-deficient adenovirus (Ad26) expressing the RSV prefusion F protein (preF) and soluble recombinant preF protein. Administered intramuscularly, the vaccine has previously been shown to induce robust humoral and cellular immunity ( Williams et al, 2020 ) and the Ad26.RSV.preF component alone shown to provide protection in a controlled human challenge model ( Sadoff et al, 2021 ).…”
Section: Short Presentations: Preventionmentioning
confidence: 99%
“…It is based on the rare human adenovirus serotype 26 and encodes the RSV F protein in its stabilized prefusion conformation. In a human challenge study, the vaccine injected intramuscularly prevented about 40% of PCR-confirmed RSV infections compared to the placebo group four weeks after immunization ( 30 ) and is now tested in a phase III clinical trial (NCT04908683). Another vaccine candidate is Moderna’s mRNA-1345.…”
Section: Introductionmentioning
confidence: 99%
“…The urgent need for rapid-response vaccines to curtail the global spread of SARS-CoV-2 put unprecedented pressure on the pharma-ceutical industry to develop and test vaccine candidates that would provide protection against disease severity and death while simultaneously demonstrating safety in vaccine recipients. Building upon existing blueprints from Ad vaccines to combat HIV, 76,161 EBOV, 87,91,162,163 influenza virus, 75,94,122 respiratory syncytial virus (RSV), 164,165 and Middle Eastern respiratory syndrome coronavirus (MERS-CoV), 166 which had already been evaluated clinically, vaccines based on Ad5, Ad26, and ChAdOx1 were constructed, manufactured, and rapidly advanced to safety and efficacy studies in early 2020. Several reviews describing the immunogenicity and efficacy of Ad-based vaccines against SARS-CoV-2 have been published 23,86 and will not be covered in detail in this review.…”
Section: Evidence For the Safety Of Adenoviral Vaccinesmentioning
confidence: 99%
“…Overall, this and other clinical trials that analyzed the safety and effi-cacy of AZD1222 vaccine concluded that the vaccine was safe and effective at preventing symptomatic and severe COVID-19. 172,173 Safety data for species D Ad26 vectors Similar to ChAdOx1, the rationale for use of Ad26 as a vaccine platform for SARS-CoV-2 was based on its low seroprevalence in humans, 152,174 its established use in clinical trials, 76,157,161,164,165 and its prior approval by the EMA as a component in a vaccine against EBOV. 82,87,90,91 The safety and efficacy of a single-dose COVID-19 vaccine Ad26.COV2.S, based on rare human adenovirus Ad26 (developed and distributed by Janssen and Johnson & Johnson), was evaluated in a series of randomized, placebo-controlled clinical trials.…”
Section: Safety Data For Chimpanzee Ad Vector Chadox1mentioning
confidence: 99%